An improved control strategy of power-frequency characteristics of virtual synchronous generator - Weiqiang Zheng; Modan Su; Changwei Gao (PLoS ONE, 2026)
A coupling relationship exists between virtual inertia J and damping coefficient D in traditional virtual synchronous generator (VSG). While a large virtual inertia enhances the VSG’s frequency support capability, it may also induce active power oscillations or significant overshoot during load power variations. To address this issue, the paper proposes an improved power–frequency characteristic control strategy for VSG. First, the mathematical model of the conventional VSG is analyzed, and a closed-loop transfer function capturing the dynamic relationship between active power and frequency fluctuation is established. The influences of virtual inertia and damping on the active power response during transient processes are systematically investigated. Second, a leading differential element is incorporated into the traditional VSG power–frequency controller, yielding an enhanced control strategy for regulating VSG power–frequency characteristics. The resulting power–frequency behavior is rigorously analyzed under both off-grid and grid-connected operating conditions. Experimental results demonstrate that, by appropriately tuning the parameters of the lead-differential element, active power oscillations during transient processes can be effectively suppressed. Moreover, the proposed strategy achieves effective decoupling between dynamic response characteristics and steady-state performance.